Motivational encouragement of self performance assessment instrument in mastering national language based on Keller's Arcs Model - Arumugam, Arul Das; Subramaniam, Vijayaletchumy (Human Resource Management Academic Research Society, 2022)
This research aims to identify the influences of using Self Performance Assessment Instrument which known in Malay language as Instrumen Penilaian Prestasi Kendiri (IPKK) on motivational encouragement for students’ learning in national language of Malaysia. Before conducting this survey, the students had a chance to use IPKK for two different tests. The survey uses the Attention (A) – Relevance (R) – Confidence (C) – Satisfaction (S) Model of Motivation, or ARCS, which was pioneered by John M. Keller. This research is quantitative-based and uses questionnaires as the main instrument. Approximately 115 students from three different schools, specifically National Type Tamil Schools or Sekolah Jenis Kebangsaan Tamil were chosen as purposive sample. They compared every item based on their experience, which is to say after and before using IPPK. The findings indicate that IPPK influenced the students’ motivational encouragement to control balancing emotions when mastering the national language. It piques their attention or desire to learn, supply appropriate knowledge, form self-confidence, and generate self-satisfaction.